2012
DOI: 10.4067/s0718-95162012000100005
|View full text |Cite
|
Sign up to set email alerts
|

The response of date palm to calcareous soil fertilisation

Abstract: An experiment was conducted during two successive seasons,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 31 publications
(22 reference statements)
8
19
1
Order By: Relevance
“…The availability of nitrogen and uptake by plants depends on the application form (Marzouk and Kassem, 2011). The results are also in line with the finding of Kassem (2012) who found that applied nitrogen in different forms alone or in combination with potassium, phosphorus and sulphur increased fruit fresh and fruit pulp weights. In addition, fruit flesh weight was increased when adding nitrogen combined with microelements on Barakawi dry date palm (Idris et al, 2012).…”
Section: Fruit Flesh Weight Volume Tss and Moisture Contentsupporting
confidence: 80%
See 2 more Smart Citations
“…The availability of nitrogen and uptake by plants depends on the application form (Marzouk and Kassem, 2011). The results are also in line with the finding of Kassem (2012) who found that applied nitrogen in different forms alone or in combination with potassium, phosphorus and sulphur increased fruit fresh and fruit pulp weights. In addition, fruit flesh weight was increased when adding nitrogen combined with microelements on Barakawi dry date palm (Idris et al, 2012).…”
Section: Fruit Flesh Weight Volume Tss and Moisture Contentsupporting
confidence: 80%
“…This may explain the reason for their effect in improving the fruit mineral content of Khenazi cultivar. Kassem (2012) obtained similar increases in fruit mineral contents by NPK alone or by its combination on Zaghloul date palm. Also, higher fruit phosphorus may be affected by nitrogen and sulphur application and enhance efficiency of soil and raise the soil total content of P, hence increase availability of P. This result agrees with Marzouk (2011) who noted that the application of elemental sulphur increased fruit phosphorus content of Zaghloul date palm.…”
Section: Fruit Nutrients Contentsupporting
confidence: 61%
See 1 more Smart Citation
“…Meier-Ploeger and Vogtmann (2003) indicated that an increase of humus content by 0.2% can cause an average increase of utilizable water capacity by 0.5% and pore volume by 1%. For sandy-textured soils where most of the MENA's date palms grow (Kassem, 2012), soils with an OM content of 4% to 5% can hold 10 times or more water and nutrients than sand soils with less OM according to the information provided by Davis and Wilson (2000). This in turn would contribute significantly to water saving efforts in the region and enable more efficiently water usage.…”
Section: Som Amendments: a Critical Key In Sustainable Management Of mentioning
confidence: 99%
“…Date palm fruits are one of the most important export fruit crops in Egypt, where they are harvested and marketed at three stages are Khalal (bisr), Rutab and Tamar (Kassem 2012). Date palm cultivars are of three main types according to its fruit moisture content and they are classified soft, semi-dry and dry cultivars (Selim et al, 1968).…”
Section: Introductionmentioning
confidence: 99%